2008
DOI: 10.1186/cc6864
|View full text |Cite
|
Sign up to set email alerts
|

An intensivist-led tracheostomy review team is associated with shorter decannulation time and length of stay: a prospective cohort study

Abstract: Introduction Without specific strategies to address tracheostomy care on the wards, patients discharged from the intensive care unit (ICU) with a tracheostomy may receive suboptimal care. We formed an intensivist-led multidisciplinary team to oversee ward management of such patients. To evaluate the service, we compared outcomes for the first 3 years of the service with those in the year preceding the service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
107
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 15 publications
7
107
1
7
Order By: Relevance
“…29 Although some specialties and institutions have found MDTs to be costly, inefficient, and lacking in evidence for a positive impact on patient outcomes, 24,27,30 one study demonstrates decreased time to decannulation and LOS for adults with tracheostomies managed by an MDT. 31 The authors concluded that MDTs allow for consensus decisionmaking, and avoid delays associated with multiple separate evaluations. 31 Another study revealed improved diagnostic workup efficiency and adherence to therapy when evidencebased guidelines were applied by an MDT in treating children with osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Although some specialties and institutions have found MDTs to be costly, inefficient, and lacking in evidence for a positive impact on patient outcomes, 24,27,30 one study demonstrates decreased time to decannulation and LOS for adults with tracheostomies managed by an MDT. 31 The authors concluded that MDTs allow for consensus decisionmaking, and avoid delays associated with multiple separate evaluations. 31 Another study revealed improved diagnostic workup efficiency and adherence to therapy when evidencebased guidelines were applied by an MDT in treating children with osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…31 The authors concluded that MDTs allow for consensus decisionmaking, and avoid delays associated with multiple separate evaluations. 31 Another study revealed improved diagnostic workup efficiency and adherence to therapy when evidencebased guidelines were applied by an MDT in treating children with osteomyelitis. 32 The American Cleft Palate Craniofacial Association and Cleft Palate Foundation has adopted organizational standards identifying characteristics of quality teams focusing on composition and function, provides organizational recognition of MDTs, and promotes a coordinated evaluation and treatment approach within the framework of the patient's overall needs.…”
Section: Discussionmentioning
confidence: 99%
“…Two further principles were adopted from previous DAS work, supported by our critical incident reviews: oxygenation of the patient takes priority (not necessarily securing the airway immediately and definitively, unless required for oxygenation); and the best assistance should be sought early [15]. Ideally, this assistance would include other members of the multi-disciplinary team who are trained and competent to deal with tracheostomy emergencies [27,45,46], working in adequately equipped clinical environments [25,31,[47][48][49].…”
Section: Results: the Guidelinesmentioning
confidence: 99%
“…Organisational changes within trusts to place tracheostomy and laryngectomy patients on to designated wards will concentrate skills, experience and equipment and provide relevant and consistent medical support, with improvements in patient care described [27,48,49,[142][143][144][145][146].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation